Intradialytic Complication and Associated Factors among Patients Undergoing Hemodialysis - Yeni Kartika Sari; Ning Arti Wulandari; Sandi Alfa Wiga Arsa; Iwit Rata Ari Dewi (Journal of Ners and Midwifery, 2021)
Hemodialysis is one of the vital management options for end-stage renal disease (ERDS) patients. Adequate hemodialysis can make a good quality of patient life. Hemodialysis patient commonly has experienced intradialytic complications, and it can be life-threatening. ESRD patients who are not compliant with fluid and dietary restrictions raised Intradialytic weight gain (IDWG), and blood pressure leads to intradialytic complications. This study aimed to determine factors associated with intradialytic complications among undergoing hemodialytic patients in Blitar. The data analysis used Multiple linear regression analysis to ascertain the possible factors that influence intradialytic complications. The sample was 55 hemodialysis patients with intradialytic complications. Based on this study, the Spearman Rank correlation test results, the factor that correlated with intradialytic complications was patient compliance with a Sig (2-tailed) value of 0.016 with a correlation coefficient value of -0.26. The correlation coefficient in the results above was negative, namely -0.263 so that the correlation between the two variables was not unidirectional. The higher compliance showed, the lower the intradialytic complications. The odds ratio (OR) value between adherence and the occurrence of intradialytic complications was 3,229. That value meant that patients with kidney failure who do not comply with the diet will have a 3-fold risk of intradialytic complications compared to patients with renal failure who comply. This result emphasizes the need for constant motivation and education at frequent intervals to ensure better adherence.